Acupoint application inhibits nerve growth factor and attenuates allergic inflammation in allergic rhinitis model rats - Wenzhan Tu; Xiaolong Chen; Qiaoyun Wu; Xinwang Ying; Rong He; Xinfa Lou; Guanhu Yang; Kecheng Zhou; Songhe Jiang (BMC, 2020)
Abstract Background Acupoint application therapy (AAT) has been widely used to treat allergic inflammation induced by allergic rhinitis (AR). The therapeutic effect of acupoint application is obvious. But the underlying therapeutic mechanism is still indistinct. Nerve growth factor (NGF) expression showed a dramatic rise in nasal mucosa tissue after AR, and allergic inflammation also increased significantly. To demonstrate how AAT can improve allergic inflammation by down-regulating the expression of NGF, AR rat models were established by intraperitoneal injection of ovalbumin (OVA) and nasal drops in SD rats. The number of nasal rubbing, sneezing and the degree of runny nose were observed and the symptoms were scored by behavioral symptom scoring method within 3 min. The expression levels of NGF and its downstream key proteins, such as IL-4, IL-5, IL-13, IgE and IFN-γ were determined by q-PCR, Western blot analysis, ELISA and immunofluorescence staining. Furthermore, H&E staining and toluidine blue staining were used to observe the pathological structure of nasal mucosa and mast cells in nasal mucosa, and the ultrastructure of nasal mucosa was observed by electron microscopy. Results Our data demonstrated that acupoint application significantly reduced the score of behavioral symptoms, and decreased the expression levels of NGF and its downstream key proteins, including IL-4, IL-5, IL-13, IgE, as well as promoting the expression level of IFN-γ in nasal mucosa tissue in AR rats. Thus, the activation of IgE and viability of mast cells was inhibited. Conclusion Our findings suggest that AAT can attenuate allergic inflammation by inhibiting the expression of NGF and its downstream pathway.